Thyroid carcinoma in nodules with Thy3 cytology: Retrospective study in a district general hospital - Pereira, Chirag (Acta Biomedica Atenei Parmensis, 2022)
Background and AimThyroid cancer is the most common malignant endocrine tumour. Fine needle aspiration cytology plays an important role in diagnosis of these tumours. The aim of the current study was to determine thyroid cancer risk for Thy3 cytology over a seven-year period from 2015 to 2021 at Royal Lancaster Infirmary, UK.Methods206 medical records with Thy3 cytology were retrospectively reviewed from January 2015 to December 2021. Patients were classified into two groups: Thy3a and Thy3f. Histopathology reports were compared with cytology reports in order to determine malignancy rates.Results18.9% of male patients and 23% of female patients had a malignant histology The average overall malignancy rate was 22.2%. More specifically, 22% of Thy3a and 22.4% of Thy3f were malignant. 22 patients eventually underwent completion thyroidectomy of which 6 patients had malignancy in the contralateral lobe.ConclusionMalignancy rates at our center was lower as compared to the national data rates.